Mengurai Kompleksitas Pemberdayaan Tanah Masyarakat: Pelajaran dari Gugus Tugas Reforma Agraria di Bangka Tengah - Sopyan, Amalia Arofah Puji; Sidipurwanty, Eliana (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
Community Land Empowerment (PTM) and the role of the Agrarian Reform Task Force (GTRA) are important to overcome inequality in land access in Indonesia. However, improving coordination between sectors is necessary to enhance the effectiveness of PTM implementation. This research aims to determine the role of GTRA in implementing PTM and various developments in access arrangements in Central Bangka Regency, as well as the problems and solutions faced. The research uses qualitative methods by collecting data through document reviews, interviews, and literature studies, as well as qualitative descriptive analysis. This research produces findings about the role of GTRA in implementing PTM to support SDGs goals through partnerships. GTRA develops access with infrastructure and non-infrastructure assistance from various agencies, such as the Department of Fisheries, Maritime Affairs, and Agriculture, as well as the Department of Housing, Settlement Areas, and Transportation, as well as capital and infrastructure assistance from the Department of Industry, Trade, Cooperatives, and UMKM. The PTM model implemented includes integrated agriculture, cross-sector collaboration, and UMKM development. GTRA faces a variety of obstacles, including a lack of community participation, changes in officials, difficulties collecting initial data, unsynchronized spatial data, time constraints, and passive village officials. Pemberdayaan Tanah Masyarakat (PTM) dan peran Gugus Tugas Reforma Agraria (GTRA) penting untuk mengatasi ketidaksetaraan akses tanah di Indonesia. Namun, koordinasi antar sektor perlu ditingkatkan untuk meningkatkan efektivitas pelaksanaan PTM. Penelitian ini bertujuan untuk mengetahui peran GTRA dalam pelaksanaan PTM dan ragam pengembangan penataan akses di Kabupaten Bangka Tengah serta permasalahan dan solusi yang dihadapi. Penelitian menggunakan metode kualitatif dengan pengumpulan data melalui telaah dokumen, wawancara, dan studi pustaka, serta analisis deskriptif kualitatif. Penelitian ini menghasilkan temuan tentang peran GTRA dalam implementasi PTM untuk mendukung tujuan SDGs melalui kemitraan. GTRA mengembangkan akses dengan bantuan infrastruktur dan non-infrastruktur dari berbagai instansi seperti Dinas Perikanan, Kelautan, Pertanian, serta Dinas Perumahan, Kawasan Permukiman, dan Perhubungan, serta bantuan permodalan dan infrastruktur dari Dinas Perindustrian, Perdagangan, Koperasi, dan UMKM. Model PTM yang diterapkan mencakup pertanian terintegrasi, kolaborasi lintas sektor, dan pengembangan UMKM. Kendala yang dihadapi oleh GTRA meliputi kurangnya partisipasi masyarakat, pergantian pejabat, kesulitan dalam pengumpulan data awal, ketidaksinkronan data spasial, keterbatasan waktu, dan perangkat desa yang pasif.